A probabilidade de falência é consistente com a teoria de trade-off? - Nakasato, Renato Hideki (2019)
Faced with the dynamism of the modern world, the academy seeks to identify an optimal capital structure to mitigate the probability of bankruptcy and maximize its profitability. However, the reality of the market dispenses with theories that explain the definition of the sources and ideal proportions of this optimal capital structure, through a combination of equity and third parties. Among these theories, we highlight the one of static trade-off that affirms that there is an optimal capital structure to be pursued by the company. The model seeks to achieve a balance between financial leverage and economic performance. Companies seek a harmonious combination of risk and bankruptcy costs and tax benefits arising from indebtedness. Thus, this study aims to verify if the theory of static trade-off is consistent for Brazilian companies that have credit rating. The hypotheses tested are: H1: The higher the tax benefit, the higher the level of indebtedness and probability of bankruptcy and H2: The lower the cost of bankruptcy, the higher the level of indebtedness and probability of bankruptcy. The verification of these hypotheses occurs through descriptive statistics, correlation analysis and logistic regressions (credit rating) and panel data (leverage). The survey sample considers 60 Brazilian non-financial companies that have credit ratings between 2010 and 2017. The data source for identifying the ratings is Bloomberg, while the other variables are obtained from Capital IQ. As a result, the variables: size, leverage and operational risks confirm the hypothesis of this research, which suggests that companies with greater earnings potential due to tax benefits and lower cost of bankruptcy opt for a capital structure with a higher probability of bankruptcy. This study contributes to the evolution of the static TOT tests in Brazil, comparing the coefficients of the determinants of probability of bankruptcy with those of the companies' level of indebtedness. Another difference found is the fact that the level of indebtedness is considered an endogenous parameter, which allows the company to reach a certain probability of bankruptcy or establish its rating.